2021
DOI: 10.1111/cea.13882
|View full text |Cite
|
Sign up to set email alerts
|

Real‐world Omalizumab and Mepolizumab treated difficult asthma phenotypes and their clinical outcomes

Abstract: Background Omalizumab and Mepolizumab are biologic drugs with proven efficacy in clinical trials. However, a better understanding of their real‐world effectiveness in severe asthma management is needed. Objectives To better understand the real‐world effectiveness of Omalizumab and Mepolizumab, elucidate the clinical phenotypes of patients treated with these drugs, identify baseline characteristics associated with biologic response and assess the spectrum of responses to these medications. Methods Using real‐wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0
7

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(41 citation statements)
references
References 35 publications
(93 reference statements)
1
33
0
7
Order By: Relevance
“…On the other hand, in severe patients in which OCS resistance is proved by a high daily dose intake, the current pharmacological armamentarium based on the use of mAbs permits reversion of OCS dependence, leading to the suspension of OCS therapy in most patients or a reduction in the daily dose greater than 50% in those subjects affected by very severe forms of asthma. In any case, the overall current real-world findings and data from specific long-term investigations [88][89][90][91] indicate that the level of the OCS-sparing effect and the reversion of OCS dependence is an effect of the mAbs class, regardless of the specific target modulated by each compound. This evidence is in agreement with the position of the current recommendations [1], which do not support one specific mAb against the others for use as an OCS-sparing agent at GINA step 5.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…On the other hand, in severe patients in which OCS resistance is proved by a high daily dose intake, the current pharmacological armamentarium based on the use of mAbs permits reversion of OCS dependence, leading to the suspension of OCS therapy in most patients or a reduction in the daily dose greater than 50% in those subjects affected by very severe forms of asthma. In any case, the overall current real-world findings and data from specific long-term investigations [88][89][90][91] indicate that the level of the OCS-sparing effect and the reversion of OCS dependence is an effect of the mAbs class, regardless of the specific target modulated by each compound. This evidence is in agreement with the position of the current recommendations [1], which do not support one specific mAb against the others for use as an OCS-sparing agent at GINA step 5.…”
Section: Discussionmentioning
confidence: 89%
“…Six studies were carried out on benralizumab [34][35][36][37][38][39], 1 on dupilumab [40], 18 on mepolizumab [41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58], 27 on omalizumab [18,, and 3 on reslizumab [85][86][87]. Four studies investigated different mAbs in the same report [88][89][90][91]. The main characteristics of the real-world studies included in this systematic review are reported in Table 1.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…It is though important to recognise that some patients don't respond to T2-biologics as recently shown by real-world studies like WATCH. 26 Understanding the mechanisms behind such failed responses will be a matter for future research focus.…”
Section: The Present-day T2 Paradigm Of Inflammation In Asthmamentioning
confidence: 99%
“…209 Real-world studies have shown that the typical patients receiving Omalizumab are younger in age, have earlyonset asthma, and had a higher reported history of co- OCS requirements [264][265][266][267][268] morbid atopic conditions such as allergic rhinitis. 20,26 The multidimensional clinical efficacy of Omalizumab in such patients has been shown in meta-analyses of clinical trials. 210 Similarly, in meta-analyses of real-world observational studies, Omalizumab response rates are around 77%, 211 with associated significantly improved exacerbation rate, FEV 1 , oral corticosteroid use, and health care utilisation.…”
Section: Omalizumabmentioning
confidence: 99%
See 1 more Smart Citation